Perbandingan Penggunaan Media Visual dan Media Audio terhadap Hasil Belajar Bahasa Indonesia Peserta Didik Kelas V MIN 1 Manggarai Flores - Wati, Ida; Ismail, Ilyas; Halimah, Andi (Primer Edukasi Journal, 2024)
The aim is to describe the final impact of learning Indonesian in class V MIN 1 Manggarai Flores which is displayed by utilizing visual media. To describe the consequences of learning Indonesian in class V MIN 1 Manggarai Flores who were educated using sound media, analyze the differences in learning outcomes in class V C MIN 1 Manggarai Flores between those displayed using visual media and those displayed using sound media. The type of inspection used in this review is a relative exploratory inspection using the Pretest-Posttest structure plan. The population in this study amounted to 58 students. The sample in this study amounted to 40 students. The testing strategy used is (Multi-stage Random Sampling). The instruments used to determine student learning outcomes are various decision tests. The information inquiry used is a clear factual checking method and an inferentially measurable inspection strategy. The results obtained at the two meetings through different factual examinations, namely the normal pretest learning outcomes of class V B students shown using visual media were 51.9, while the posttest normal scores were 79.25 with a difference of 27.35. The normal pretest learning outcomes for class V C students displayed using sound media were 44.5, while the posttest normal scores were 71.2 with a difference of 26.7. The results of the information speculation test after the use of visual media and audio media at two meetings with measurements obtained a critical value of 0.008 and a large level value of 0.05. So it is suspected that there is a very large difference in learning outcomes in class V B which is displayed using visual media and class V C which is displayed using sound media.